Phosphorus availability in soils, determined by different extracting procedures - Silva, Fábio Cesar da; Raij, Bernardo Van (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this paper was the comparative study of the most important extractors of soil phosphorus. It presents a literature review of papers that deal with methods of extraction for the evaluation of phosphorus availability in soils. The methods considered were: anion exchange resin, Olsen, Bray 1, Bray 2, Mehlich 1, Troug, Égner, water, 0,01M CaCl2, iron hydroxide impregnated filter paper (Pi) and the determinations of the E and L values. The comparison between results of soil analysis by different methods of phosphorus extraction in soils and phosphorus uptake by plants was initially made considering the coefficient of determination (r2) for several extractants. The following average values and corresponding numbers of articles in which the method was considered were obtained: resin, 70% (34); E value, 68% (16); L value, 65% (8); Olsen, 54% (48); Bray 1, 50% (42); Mehlich 1, 46% (25); Égner, 44% (9); Bray 2, 42% (19); Water, 42% (15); Truog, 38% (13); CaCl2, 36% (13), and Morgan, 32% (13). The comparison of several methods, considering the pairs of results (r2) obtained for the extractants, that were tested together through linear correlation and average contrasts (t student test), indicated that the resin method was statistically superior to the other methods. The resin method presents the following favorable features: (a) highest values for the determinations coefficients for the correlations between P uptake by plants and soil P by the different methods, as reviewed in 72 papers; (b) it can be used in both acid and alkaline soils, which is not the case for the other most commonly used methods; (c) it reveals adequately the effect of liming on the increase of P availability in soils for crops, which is not the case of Mehlich 1, Bray 1 and Olsen; (d) it does not overestimate P availability in soils treated with rock phosphates, as is the case of acid extractans; (e) it is the method with the best theoretical background.